The effects of a standardized nursing intervention model on immobile patients with stroke: a multicenter study in China. (December 2019) - Liu, Hongpeng; Zhu, Dawei; Cao, Jing; Jiao, Jing; Song, Baoyun; Jin, Jingfen; Liu, Yilan; Wen, Xianxiu; Cheng, Shouzhen; Nicholas, Stephen; Wu, Xinjuan
Background: Immobility complications, including pressure injuries (PIs), deep vein thrombosis (DVT), pneumonia, and urinary tract infections (UTIs), affect the clinical outcomes of stroke patients. A standardized nursing intervention model (SNIM) was constructed and implemented to improve the quality of care and clinical outcomes among immobile patients with stroke. Aims: To assess the benefit of SNIM for immobility complication rates, including PIs, DVT, pneumonia, and UTIs, and mortalities in immobile patients with stroke. Methods: A before and after study design was used. Patients were divided into a pre- and post-SNIM training original cohort and matched for socioeconomic, demographic, and disease characteristics using propensity score. We fitted logistic regression models to examine the effect of SNIM, and whether the benefit differed between tertiary and non-tertiary hospitals. Results: In the original cohort, the rate of pneumonia, UTIs, and mortality was lower after SNIM training. Furthermore, in the matched cohort, the difference in PI rates was significant. Logistic regression analysis revealed that the probability of PIs, pneumonia, UTIs, and mortality were significantly reduced after SNIM training in the original cohort and this estimated value changed little in the matched cohort. Our results show that the decreased rates of pneumonia, UTIs, and mortality were mainly among non-tertiary hospitals. Conclusions: A structured and systematic SNIM benefited immobile stroke patients' clinical outcomes, but mainly in non-tertiary hospitals in China. Standardized nursing training is needed in non-tertiary hospitals.